COPYRIGHT PROTECTION FOR NON-FUNGIBLE TOKENS AS DIGITAL ARTWORKS - Halim, Chandera; Sukmaningrum, Anastasia Angger (DAS Institute, 2024)
The current technological developments have provided convenience for society in accessing the internet, which can be utilized in various fields, one of which is the economy. In economic activities through digital media, the term